PERBEDAAN PENAFSIRAN DALAM IMPLEMENTASI FATWA NOMOR 23/2002 TENTANG POTONGAN PELUNASAN PADA AKAD MURABAHAH: Studi Perbandingan Lembaga Bank di Kota Malang - Tiyasasih, Devitha Angesti (Jurisdictie: Jurnal Hukum dan Syariah, 2017)
Home Financing includes long-term financing that enables the Customer to repay before maturity. This product uses Murabahah principle and based on Fatwa Dewan Syariah Nasional allows for accelerated repayment. Unlike Conventional Banks that impose penalties on accelerated repayment, Bank Syariah provides a deduction for the debt. This study discusses the difference of interpretation between Bank Syariah in implementing Fatwa Number 23/2002 about deduction of payment in Murabahah, sanction of supervision from related institution concerning violation of fatwa and enforcement effort. Research shows that the Bank interprets grammatically with different results, at Bank Muamalat the price discount should not be promised either on the murabaha contract or the internal provisions while the Bank Syariah Mandiri also does not put a clause on the contract but make provisions in the form of internal procedures. The deductions are based on the balance sheet of the Bank and the character of the customer during the period of financing, and if there is a violation, the National Sharia Board shall not sanction but report to the banking regulator, Bank Indonesia and the Financial Services Authority.